Space frame structures in domestic design practice and their installation methods - S. S. Potasiev (Vestnik MGSU)
Introduction. Modern construction demonstrates the wide use of various space frame types, because of their efficient from an engineering point of view, architecturally expressive, economical and durable. Large spans required increased frame rigidity; in such situations, space frames are more economical than classic flat trusses solutions. The most economical, both in material consumption terms and in the work cost are sparse structures. Such constructions meet all industrial and civil buildings requirements and have short building period. Not all safety requirements meeting building algorithm can be developed on currently existing technical base. More than that, domestic norms base does not include construction loads calculation methods. Critical differences in structures types determine building organization process but there are only general space frame building recommendations in domestic technical literature.Materials and methods. The space frame advantages and disadvantages are considered, the main area of application of this type of structures is determined. On the basis of material consumption and the most commonly used spans in modern buildings and structures research results, it was decided to study standard solutions developed by domestic research institutes. The main technical characteristics of structural blocks of the most common series are described. The main disadvantage of space-grid structures in general is the installation technology, so the methods of their installation are considered. The advantages and disadvantages of each method are analyzed, their field of application is determined.Results. The review and analysis of existing structural systems, including serial solutions of coverings and methods of their construction are performed. The most optimal method choosing criteria for structural blocks erection are determined. It was revealed that serial structural blocks such as “Kislovodsk” and “Moscow” do not have an exact installation algorithm. Therefore, an individual project is developed for the buildings with such coverings.Conclusions. The currently existing technical base is not enough to develop erecting structures algorithm that meets all safety requirements, and calculations for construction loads have not yet been made on its basis. To date, there are general provisions that have been developed for all coverings, but their use often becomes extremely dangerous due to critical differences in the types of structures.